Lifestyle and environmental risk factors for myopia in children: Evidence from a large-scale cross-sectional study in Shandong, China - Wance Wang; Jiahao Gong; Lei Yan; Bowen Xu; Yanqun Shi; Renkai Ge (PLoS ONE, 2026)
Myopia has emerged as a pressing global public health issue, with a particularly sharp rise observed among school-aged children. This period represents a critical window for implementing timely, evidence-based interventions to slow myopia progression and mitigate the risk of high myopia. This study aimed to investigate the prevalence and associated risk factors of myopia among children aged 9–12 years in Shandong Province, China, with a specific focus on the roles of demographic characteristics, environmental exposures, and behavioral patterns. A cross-sectional survey was conducted in 2024 using a stratified cluster sampling design. A total of 77,629 children from 16 cities were enrolled. Data collection included standardized visual acuity assessments and structured questionnaires. Multivariate logistic regression models were used to examine the associations between behavioral factors and myopia. Only variables that showed significant associations in univariate (chi-square) analyses were included in the models, without additional adjustment for other potential confounders. The overall prevalence was 41.24%, increasing with age and reaching 44.34% at 12 years. Significant demographic risk factors included female sex (OR=1.030,95%Cl = 1.001–1.060), urban residency (OR=1.045,95%Cl = 1.014–1.077), and parental myopia, particularly when both parents were affected (OR=1.320,95%Cl = 1.270–1.372). Behavioral risk factors included reading while lying down (OR=1.093,95%Cl = 1.035–1.154), screen exposure exceeding three hours per day (OR=1.058,95%Cl = 1.010–1.109), and homework duration over three hours per day (OR=1.072,95%Cl = 1.033–1.112). Protective factors comprised outdoor activity five or more times per week (OR=0.898,95%Cl = 0.865–0.932), maintaining proper posture during reading and writing (OR=0.925,95%Cl = 0.898–0.952), screen viewing distance over three meters (OR=0.933,95%Cl = 0.905–0.961), and sleeping at least eight hours per night (OR=0.918,95%Cl = 0.876–0.961). These findings underscore the multifactorial etiology of myopia, shaped by environmental, and behavioral influences. They highlight the urgent need for comprehensive and targeted interventions, particularly for high-risk groups. This study provides robust empirical evidence to inform region-specific myopia control strategies and supports the development of public health policies aimed at improving pediatric vision health.